2021
DOI: 10.1186/s13287-021-02181-4
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin activates ABCA1 via the BiP/NRF1 pathway to suppress high-cholesterol-induced apoptosis of mesenchymal stem cells

Abstract: Background Retarded wound healing in patients with obesity contributes to a risk of complications associated with vascular insufficiency and oxidative stress. The high cholesterol levels of patients with obesity are associated with apoptosis of engrafted umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs). Melatonin contributes to the prevention of cholesterol accumulation in patients with obesity via a mechanism that is poorly understood. We therefore investigated the regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Cell precipitates were stained with 0.1% trypan blue (Beyotime, Shanghai, China) as described. The live cell rate (%) was calculated as the number of living cells (trypan blue-negative cells)/the total cell number [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell precipitates were stained with 0.1% trypan blue (Beyotime, Shanghai, China) as described. The live cell rate (%) was calculated as the number of living cells (trypan blue-negative cells)/the total cell number [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Improved wound healing in the skin was achieved by transplanting umbilical cord MSCs with support by melatonin treatment [18]. Hepatic tissue repair for the purpose of ameliorating liver fibrosis was performed with melatonin-preconditioned BMSCs [14] or dental pulp MSCs [12].…”
Section: Reprogramming and Therapeutic Use Of Mscsmentioning
confidence: 99%
“…The present article will not discuss in detail all the different aspects of melatonin effects in connection with stem cells. For instance, a number of studies has dealt with adjunctive roles of melatonin for the success of transplantation or injection of stem cells at injured or dysfunctional sites [10][11][12][13][14][15][16][17][18]. Similarly, the antioxidant and anti-inflammatory properties of melatonin have been taken as a reason for protecting stem cells against oxidative and inflammatory insults [13,15,[19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other effects of melatonin were recently demonstrated on mesenchymal stem cells derived from the umbilical cord blood of obese rodents that reduce cholesterol accumulation and prevent apoptosis of MSCs, supporting the therapeutic role of melatonin against obesity. 78 A recent meta-analysis of the effects of melatonin in human obesity studies showed that, despite the evidence found in the energy balance of rodents and humans, 79,80 the real impact of melatonin on body weight loss remains unclear due to the inconsistent melatonin treatment schedule regarding duration and low dose (0.01-0.1 mg kg −1 day −1 ) in all studies. Overall, these data provide evidence that, under melatonin treatment, the de novo differentiation of beige cells in ZDF rats and humans probably occurs in conjunction.…”
Section: Papermentioning
confidence: 99%